Quatre décennies de « coopération franco-africaine » : usages et usure d'un clientélisme - Petiteville, Franck (Études internationales, 1996)
Since 1960, the French African Policy has been based on a military, economic, and cultural cooperation. Behind the official goal, that of development aid, lie the French geopolitical priorities. Since general de Gaulle, the French diplomacy is obsessed by the international place of France in the World. The influence of France in Africa is an integral part of this. Therefore the cooperation between France and Africa is clientelist : the economic and financial aid provided by France is exchanged with the French privilege of an economic and political influence within the African states, which includes military support in situations of border conflict and even domestic « disorder ». This conception of the relationship between France and Africa has not really changed with the French presidents who have followed general de Gaulle. Consequently, the French government institutions of cooperation with Africa have been in the same situation since the sixties. The result is such a complex, obsolete and inefficient labyrinth that the real execution of French African policy is carried out in non-official political and business networks. A radical reform of this policy is now necessary, due to the new international context : the end of the Cold War, the French involvment in the European process, and the increasing dependance of Africa on the Bretton Woods institutions.